Case-Control Research on Hypertension Risk Factors in Karangasem Village, Karangasem Regency, Bali - Adhikara, Wayan Satwika (WMJ (Warmadewa Medical Journal), 2020)
Hypertension is still a health problem globally. Several studies have been conducted to find the relationship between risk factors with the incidence of hypertension. There is no data yet on risk factors for hypertension in the community, especially in Karangasem Regency, Bali. This study aims to find the correlation of various risk factors with the incidence of hypertension in Karangasem Regency, Bali. A case-control studies was conducted on 100 subjects. Cases and controls were selected using consecutive sampling technique. Logistic regression was used to predict various risk factors for hypertension. The results showed a significant relationship with age (OR = 2,452; p = 0.047; 95% CI = 0.999-6.018), family history (OR = 4,373; p = 0.001; 95% CI = 1,854-10,316), BMI (OR = 3,341; p = 0.004; 95% CI = 1,440-7,753), smoking (OR = 2,698; p = 0.021; 95% CI = 1,148-6,341), high salt consumption (OR = 2,571; p = 0.024; 95% CI = 1,122 -5,895) and coffee consumption (OR = 3,451; p = 0.016; 95% CI = 1,220-9,759), while no significant relationship was found between sexes (OR = 0.712; p = 0.476; 95% CI = 0.279 - 1,818), and alcohol consumption (OR = 0.786; p = 0.548; 95% CI = 0.358-1.725). We found an association between several risk factors (age, family history, BMI, smoking, high salt consumption, and coffee consumption) and the incidence of hypertension in the Karangasem Village, Karangasem Regency, Bali.